Peripheral and Site‐Specific CD4+CD28null T Cells from Rheumatoid Arthritis Patients Show Distinct Characteristics. (February 2014) - Pieper, J.; Johansson, S.; Snir, O.; Linton, L.; Rieck, M.; Buckner, J. H.; Winqvist, ‎O.; van, R.; Malmström, V.
Abstract Proinflammatory CD4+CD28null T cells are frequently found in the circulation of patients with rheumatoid arthritis (RA), but are less common in the rheumatic joint. In the present study, we sought to identify functional differences between CD4+CD28null T cells from blood and synovial fluid in comparison with conventional CD28‐expressing CD4+ T cells. Forty‐four patients with RA, displaying a distinct CD4+CD28null T cell population in blood, were recruited for this study; the methylation status of the IFNG locus was examined in isolated T cell subsets, and intracellular cytokine production (IFN‐γ, TNF, IL‐17) and chemokine receptor expression (CXCR3, CCR6 and CCR7) were assessed by flow cytometry on T cells from the two compartments. Circulating CD4+CD28null T cells were significantly more hypomethylated in the CNS‐1 region of the IFNG locus than conventional CD4+CD28+ T cells and produced higher levels of both IFN‐γ and TNF after TCR cross‐linking. CD4+CD28null T cells from the site of inflammation expressed significantly more CXCR3 and CCR6 compared to their counterparts in blood. While IL‐17A production could hardly be detected in CD4+CD28null cells from the blood, a significant production was observed in CD4+CD28null T cells from synovial fluid. CD4+CD28null T cells were not only found to differ from conventional CD4+CD28+ T cells in the circulation, but we could also demonstrate that synovial CD4+CD28null T cells showed additional effector functions (IL‐17 coproduction) as compared to the same subset in peripheral blood, suggesting an active role for these cells in the perpetuation of inflammation in the subset of patients having a CD28null population.